Macarie Bulgakov – Teologia Dogmatică Ortodoxă, 2 vol., trad. de arhim. Gherasim Timuş, Tipografia Cărţilor Bisericeşti, Bucureşti, 1886-1887, 767 + 870 p. Analiză - But-Căpușan, Dacian (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2019)
For the Romanian Orthodox Theology, in general, and for the Dogmatic one, in particular, the translation of the Orthodox Dogmatic Theology of the Russian dogmatist Macarie Bulgakov marked an important moment, with a long-term impact, this work being con- sidered one of the most important. It was used as a rule in all the higher theological schools in the Orient, considered even at the beginning of the twentieth century the most dog- matic scholar in the Orthodox Dogmatic Theology. Although it was elaborated more than a century and a half ago, the treatise that totals over 1600 pages contains valuable elements about fundamental aspects of the teaching of orthodox faith, remaining, despite the school spirit in which it was written, specific to that period, a useful working tool, with a wealth of valuable information.